Analisis Pelaksanaan Aplikasi E-office dan E-dokument di RSUD Siti Fatimah Provinsi Sumatera Selatan - Alhadi, Bahrudin; Saswita, Saswita; Febrianza, Muhammad (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
This thesis is entitled “Implementation Analysis ApplicationE-office AndE-dokument At the Siti Fatimah Hospital in South Sumatra Province.